Applied spatial analytic tools in orchards with special regard to agro-ecology - Fórián, T.; Nagy, A.; Tamás, J.; Szabó, Z.; Soltész, M.; Nyéki, J. (International Journal of Horticultural Science, 2011)
Our investigation was carried out in several orchards in Hungary. This study reviews applicability of the different spatial analytical techniques in orchard especially models based on surface relief, such as digital elevation model, digital terrain model, slope and aspect maps. In recent time, the generation of digital elevation model has become a popular examination method. However, the elevation models generated from contour lines or elevation points could be applied to evaluate agro- ecological potential of fruit orchards to some extent. The highest deficiency of these models is the fact that these show the altitude of soil surface only and do not demonstrate landmarks on the surface. Consequently, the calculation of the radiation value results data relating to soil surface. The terrain model generated and applied by our team demonstrates fine surface texture and the landmarks in the orchard, so it is suitable for further examination.